Betatrophin: A promising biomarker for metabolic syndrome and diabetes mellitus risk screening in teenagers - Hendra Susanto; Aulanni’am Aulanni’am; Dyah Kinasih Wuragil; Ahmad Taufiq; Sunaryono Sunaryono; Jerry Dwi Trijoyo Purnomo; Dyah Ika Krisnawati; Moch Sholeh (Indonesian Journal of Medical Laboratory Science and Technology)
Metabolic syndrome (MetS) and diabetes mellitus (DM) have become primary concerns worldwide, especially among the younger population. The Indonesian Boarding School model (IBS/Boarding School) is a large education system with a significant number of pupils (teenagers) and has the potential to become a center for metabolic disease, particularly among teenagers, due to their daily intake. This study aimed to provide a baseline screening for MetS and the risk of DM development in Boarding School teenagers. During this observational study, 90 healthy serological samples were obtained from senior and junior high school students. The circulating level of betatrophin was measured using a human betatrophin ELISA kit. Additionally, metabolic syndrome and DM screening data were analyzed using a rapid reverse-flow immunochromatography kit for 65 kDa glutamic acid decarboxylase (GAD65). Among the 90 healthy students, a high prevalence of GAD65 was observed, indicating a potential risk factor for metabolic diseases. Furthermore, higher serum betatrophin levels were observed in the samples. The circulating level of betatrophin was found to have a significant correlation with age, gender, body mass index (BMI), systolic blood pressure (SBP), fasting blood glucose (FBG), sleeping duration, and duration of stay at Boarding School (p < 0.05). Betatrophin emerged as a potential predictor of BMI, SBP, and FBG in students (p < 0.05). Both betatrophin and GAD65 have shown promise as future biomarkers, opening up a new avenue for assessing metabolic syndrome and the risk of DM. This underscores the importance of future programs in Boarding Schools focusing on MetS and DM prevention management, making the audience feel the significance of their work in addressing these pressing health issues.